Potential gain in life expectancy by eliminating the endocrine nutritional and metabolic diseases in Southern States of India - Kumar, Salabha S.; K., Preethi (International Journal Of Community Medicine And Public Health, 2025)
Background: Over the past century, non-communicable diseases have emerged as the primary cause of death globally. Among them, Endocrine, Nutritional and Metabolic diseases have shown an increasing trend from 2017 to 2020, likely the ranking rising from the 8th to the 5th in the MCCD data. In southern India, people are living longer, but not always healthier. Diabetes and thyroid disorders are silently shortening lives, often without drawing the attention they deserve. Methods: The estimated data for India was extracted from the Medically Certified Data (MCCD)2020. The gain in life expectancy is calculated by following the elimination method (Shuji Hashimoto et al, 2012). Abridged Life tables were constructed using Chaing’s method in the United Nations’ software package for mortality measurements (MORTPAK). For the construction of the life table, first, calculate the nqx values from the observed age-specific death rates nmx. A life table that eliminated deaths caused by disease was constructed using data on the number of deaths and life tables without disease elimination. The study is a cohort study that was conducted from January 2024 to August 2024. Results: The potential gain in life expectancy ranges from 0 to 7.84 years. By comparing other southern states, Tamil Nadu witnessed drastic changes in the life expectancy of males (7.84 years) and females (0 years) in the age group 25 to 35 age group. Conclusions: The significant impact of Endocrine Nutritional and Metabolic diseases on mortality and life expectancy across southern Indian states, underlining the critical need for healthcare interventions.